Birth of a norm champion: how South Africa came to support the NPT's indefinite extension. Issue 1 (2nd January 2019) - Onderco, Michal; Van Wyk, Anna-Mart
ABSTRACT: In 1995, South Africa was in a special position. It was: a new party to the Treaty on the Non-Proliferation of Nuclear Weapons (NPT), the first country to voluntarily renounce nuclear weapons, led by a charismatic leader, and seen as a champion of disarmament principles. Yet South Africa's new leaders were also interested in affirming their position within the Non-Aligned Movement, which was adamantly opposed to the NPT's indefinite extension. Why, then, did South Africa decide to support the indefinite extension of the NPT in 1995? Existing scholarship has ascribed too much credit to pressure from the United States, overlooking domestic debates in South Africa and the bifurcation between professional diplomats and political elites. This article, building on new archival sources and in-depth oral-history interviews with major actors, demonstrates that South African diplomats opposed indefinite extension while South African policy elites allocated little attention to the topic until late in the game. The findings contribute to our understanding of South Africa's norm entrepreneurship, as well as the politics of global nonproliferation.